(3VeGfGJ GdeJge CeGe GdeMceI GdLfGFjI GdOhdjI (B/ s - (3YHOGddg MSjf aQMGJs; (3TQja SjO cGeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3jcJSi GdHMK aj ehVhY VeGfGJ GdeJge CeGe GdeMceI GdLfGFjI GdOhdjI CgejI bUhi HGYJHGQg jHjf GdeYGjjQ GdOhdjI ddeMceI GdLfGFjI GdYGOdI ef NdGd QUO GdMbhb PGJ GdYdGbI HMeGjI GdaQO (B((3GdeJge(B) (3aj eNJda eQGMd GdELQGAGJ GdLfGFjI(B: (3GdJj JJNP ef bHd GdeMceI GdLfGFjI GdOhdjI GJLGgg h HjGf GdCKQ GdeJQJH Ydi YOe eQGYGI Jdc GdMbhb(B. (3aGdeJge EfSGf h jLH Cf jMXi HVeGfGJ CKfGA eKhdg CeGe GdeMceI JWHjbG deHGOF Mbhb GdEfSGf GdhGQOI aj GdehGKjb h GdeYGgOGJ GdOhdjI HOGjI HGdEYdGf GdYGdei dMbhb GdEfSGf efP YGe 1948es
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B202-218s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdeMceI GdLfGFjI GdOhdjIs; (3GdfXGe GdCSGSi ddeMceI GdLfGFjI GdOhdjIs; (3VeGfGJ GdeJges; (3GdeOYj GdYGe s; (3GdGSJLhGH s; (3ELQGAGJ GdJMbjb GdGMJjGWjI s; (3eQMdI GdeMGceI s; (3GdeMGceI GdYGOdI s; (3VeGfGJ JfajP GdYbhHIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs